TINJAUAN HUKUM TERHADAP KEJAHATAN YANG DILAKUKAN OLEH ANAK TERLIBAT GENG MOTOR MENGAKIBATKAN KERUSAKAN BARANG (Study Kasus Putusan Pengadilan Negeri Medan Nomor 2.634/Pid.B/2012/PN.Mdn) - Lubis, Elvi Zahara; Marsella, Marsella; Nico, Nico (Universitas Medan Area, 2014)
Efforts to authorized law enforcement officers in tackling crimescommitted by motorcycle gangs in Medan, covering preventive and repressive.The cause of crimes of violence committed by children in the form of solidaritywith his friends who joined o motorcycle gang, as well as the lack ofsupervision of the association of parents of child.